Evaluation of fire lookout towers using GIS-based spatial visibility and suitability analyzes : Procjena tornjeva za nadzor požara pomoću analize prostorne vidljivosti i prikladnosti potpomognute GIS-om - Akay, Abdullah Emin (Array, 2020)
Effective forest fire fighting involves alerting firefighting teams immediately in the case of a fire so that teams can promptly arrive the fire scene. The most effective way for an early detection of forest fires is monitoring of forest lands from fire lookout towers. Especially in fire sensitive forest lands, towers should be systematically located in such a way that fire lookout personnel can monitor the largest amount of forest land as possible. In this study, the visibility capabilities of lookout towers located in Köyceğiz Forest Enterprise Directorate (FED)in the city of Muğla in Turkey were evaluated by using Geographical Information System (GIS) based visibility and suitability analysis. The results of visibility analysis indicated that 77.12% of forest land were visible from the current towers. To extend the proportion of visible forest lands, locations of additional lookout towers were evaluated using spatial visibility and suitability analysis in which the tower locations were examined by considering specific criteria (i.e. distance to roads, elevation, ground slope, topographic features). Suitability analysis results identified five new towers in addition to current towers in the study area. The results indicated that visible forest lands increased to 81.47% by locating new towers, and increase of almost 4.35%. In addition, over half of the forests became visible by at least two towers when including five towers suggested by suitability analysis. The GIS-based method developed in this study can assist fire managers to determine the optimal locations for fire lookout towers for effective fire management activities.